2017
DOI: 10.1016/j.biomaterials.2016.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity evaluation of magnetic hyperthermia induced by remote actuation of magnetic nanoparticles in 3D micrometastasic tumor tissue analogs for triple negative breast cancer

Abstract: Magnetic hyperthermia as a treatment modality is acquiring increased recognition for loco-regional therapy of primary and metastatic lung malignancies by pulmonary delivery of magnetic nanoparticles (MNP). The unique characteristic of magnetic nanoparticles to induce localized hyperthermia in the presence of an alternating magnetic field (AMF) allows for preferential killing of cells at the tumor site. In this study we demonstrate the effect of hyperthermia induced by low and high dose of MNP under the influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 49 publications
1
22
0
Order By: Relevance
“…This phenomenon of a more uniform distribution of MNPs after the AMF exposure has also been previously observed in a spheroid model of triple negative breast cancer. 34 It has also been previously reported on a in vivo model where the nanoparticles where initially located in the collagen-rich outer areas of the tumour and penetrated more deeply into the core after the hyperthermia treatment. 47 The enhancement of the MNP uptake may be associated with an increase in collagen permeability induced by the temperature rise during the MH treatment making the MNPs more "accessible" to the cells.…”
Section: Table 1 Percentage Of Cells That Contain Mnps In the Inandoutmentioning
confidence: 73%
“…This phenomenon of a more uniform distribution of MNPs after the AMF exposure has also been previously observed in a spheroid model of triple negative breast cancer. 34 It has also been previously reported on a in vivo model where the nanoparticles where initially located in the collagen-rich outer areas of the tumour and penetrated more deeply into the core after the hyperthermia treatment. 47 The enhancement of the MNP uptake may be associated with an increase in collagen permeability induced by the temperature rise during the MH treatment making the MNPs more "accessible" to the cells.…”
Section: Table 1 Percentage Of Cells That Contain Mnps In the Inandoutmentioning
confidence: 73%
“…These results emphasize the importance of cell environment as an essential variable to consider in future studies evaluating nanoparticle toxicity, including MWCNT toxicity. Several groups have identified novel in vitro 3D cell culture techniques to recapitulate tissue-like structures that can provide a more accurate evaluation of nanomaterial toxicity (Dubiak-Szepietowska et al, 2016; Lee et al, 2009; Muoth et al, 2016; Stocke et al, 2017; Wills et al, 2016). More specifically in regards to MWCNT toxicity, and in agreement with our findings, investigators using Schwann cells grown as monolayers or using cells embedded in CNT-loaded scaffolds(Behan et al, 2011) concluded that SWCNTs decreased proliferation and altered Schwann cell morphology in a monolayer, whereas exposure to SWCNTs in a 3D scaffold did not affect cell proliferation, viability, or morphology.…”
Section: Discussionmentioning
confidence: 99%
“…In view of our knowledge and understanding of the tumor microenvironment, Sethi et al have structured a three-dimensional (3D) co-culture system which consists of mCherry fluorescent-protein-expressing 4T1 tumor cells, green fluorescence protein (GFP)-expressing C166 endothelial cells, and murine embryonic fibroblasts [ 62 ]. With the existence of an alternating magnetic field, a high concentration of magnetic nanoparticles (about 1 mg/mL) showed enhanced cell killing, indicating the potential in thermal therapy for secondary lung malignancies [ 63 ]. Epidermal growth factor receptor (EGFR) overexpression is a general phenomenon in non-small cell lung cancer patients, and it is convenient to utilize nanoparticles-containing inhalable aerosols for lung cancer therapy through the gas exchange of the lungs [ 64 ].…”
Section: Multiple Ways With Nanoparticles For Treatment Of the Thrmentioning
confidence: 99%